2007
DOI: 10.1111/j.1365-294x.2006.03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of population differentiation in seabirds

Abstract: Despite recent advances in population genetic theory and empirical research, the extent of genetic differentiation among natural populations of animals remains difficult to predict. We reviewed studies of geographic variation in mitochondrial DNA in seabirds to test the importance of various factors in generating population genetic and phylogeographic structure. The extent of population genetic and phylogeographic structure varies extensively among species. Species fragmented by land or ice invariably exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
350
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(375 citation statements)
references
References 120 publications
21
350
1
3
Order By: Relevance
“…arminjoniana on Trindade and Round island shows significant population structure between them, in the form of a significant F ST value (Brown et al, submitted-b). However, this structure is weak when compared with other Procellariiform species which have populations in different ocean basins (Friesen et al, 2007), supporting the theory that the two populations of Pt. arminjoniana have recently split from one another (Brown et al, submitted-b).…”
Section: Procellariaesupporting
confidence: 57%
“…arminjoniana on Trindade and Round island shows significant population structure between them, in the form of a significant F ST value (Brown et al, submitted-b). However, this structure is weak when compared with other Procellariiform species which have populations in different ocean basins (Friesen et al, 2007), supporting the theory that the two populations of Pt. arminjoniana have recently split from one another (Brown et al, submitted-b).…”
Section: Procellariaesupporting
confidence: 57%
“…Seabirds from the South American mainland, however, tend to forage in the nearby and highly productive upwelling zone along the continental shelf [41], so many of them may not venture out far from the coast. A recent review of seabird population structuring [42] found that most populations occupying separate ranges during the non-breeding season also display population genetic structure. Our results regarding the Galapagos population could thus be explained by geographical/ foraging range isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, these flyways have been delimited based on mark-recapture data but, in many species, they are also supported by the molecular data (mostly mtDNA), that is, in passerines (Ruegg and Smith, 2002;Clegg et al, 2003;Pérez-Tris et al, 2004), waders (Wennerberg, 2001) and several species of waterfowl (Scribner et al, 2001;Gay et al, 2004). Similarly, Friesen et al, (2007) found that a majority of seabirds with discontinuous distributions on the breeding or wintering grounds showed some genetic substructure. Sometimes, genetic divergence across migratory divides is only observed for one marker type, typically mtDNA in species with male-biased dispersal (Scribner et al, 2001;Gay et al, 2004), but we are aware of only two other studies where it was absent altogether (Pearce et al, 2004;Liu et al 2011).…”
Section: Genetic Differentiation and Migratory Dividesmentioning
confidence: 95%